PEMBUATAN SABUN DENGAN EKSTRAK ETANOL DAUN KERSEN (MUNTINGIA CALABURA) SEBAGAI ANTISEPTIK ALAMI - Putri, Elisa; Amilda, Putri; Lubis, Meutia Putri; Astari, Weni (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
Liquid soap is a liquid skin cleansing preparation made from soap base with the addition of other permitted ingredients and is used to cleanse the skin without causing irritation to the skin which can be caused by bacteria. This study aims to determine the effect of the addition of ethanol extract of kersen leaves in liquid soap preparations against Staphylococcus aureus bacteria. Liquid soap formulation of ethanol extract of kersen leaves (Muntingia calabura) was formulated in 3 (three) formulations, namely F1 soap preparation with 25% extract concentration, F2 with 30% kersen leaf ethanol extract concentration, and F3 with 35% kersen leaf ethanol extract concentration. Antibacterial testing was carried out using the disc diffusion method. The results of the antibacterial activity test of antiseptic liquid soap preparations F1 soap preparation has an inhibition of 16.82 mm, formulation 2 30% extract concentration has an inhibition of 19.52 mm, F3 extract concentration has an inhibition of 21.90 mm and positive control Dettol soap has an inhibition of 22.22 mm against Staphylococcus aureus bacteria. The conclusion of this study is that ethanol extract of kersen leaves has antibacterial activity against Staphylococcus aureus bacteria and the most optimal inhibitory concentration is kersen leaf extract soap preparation with a concentration of 35% with a very strong inhibition zone category.